Case report: Concurrent low-volume subdural hematoma and ipsilateral ischemic stroke presenting as capsular warning syndrome: a complex case with anticoagulation dilemma and dual pathology - Strahnen, Daniel; Stathi, Angeliki; Beck, Jürgen; Roelz, Roland; Vasilikos, Ioannis (Frontiers in Neurology, 2024)
Background The simultaneous emergence of low-volume subdural hematoma and ipsilateral ischemic stroke in an atrial fibrillation patient who is under anticoagulation therapy is a rare and intricate clinical case. This report accentuates the diagnostic and treatment complexities associated with these consecutive neurological conditions. Case presentation An 83 years-old male patient initially presented with acute dyspnea, raising the suspicion of pulmonary embolism. After exclusion of pulmonary embolism through CT angiography, the patient experienced a sudden onset of left-sided hemiparesis without prior history of head trauma but with chronic intake of apixaban due to atrial fibrillation. Subsequent cranial CT tomography revealed a small right parietal subdural hematoma. After reversal of the anticoagulation therapy, surgical evacuation of the subdural hematoma was successfully performed. However, in the postoperative period, the patient developed new neurological symptoms that could not be explained by the reduced size of the subdural hematoma on a follow-up CT scan. Cranial MRI revealed the coexistence of acute ischemic stroke in the right corona radiata. The recent surgical procedure precluded guideline-recommended stroke treatment. Discussion This case underscores the complexities of diagnosing and treating concomitant small volume subdural hematoma and ischemic stroke, especially if the latter occurs in the corona radiata resulting in fluctuating symptoms known as “capsular warning syndrome.” Reversal and secondary discontinuation of anticoagulant therapy for surgical intervention highlight the inherent risk of thrombotic events in anticoagulated patients. The development of tailored treatment strategies requires a multidisciplinary approach, and further research and guidelines are required in similar complex scenarios. Conclusion The presence of both a small subdural hematoma and an ipsilateral ischemic stroke presenting as capsular warning syndrome in an anticoagulated patient highlights the intricacy of their care. This case calls for a comprehensive and collaborative strategy to address complicated clinical scenarios.